Platelet Metabolism during the Interiorization of Two Different Types of Particulate Matter - Cooper, I. A.; Cochrane, P; Firkin, B. G.; Pinkard, K. J. (Thrombosis and Haemostasis, 1972)
It has been suggested that human platelets possess the ability to phagocytose particulate matter similar to the polymorphonuclear leukocyte. However some difference of opinion has arisen regarding this contention, particularly as differences have been demonstrated with regard to the observed metabolic changes occurring in platelets related to such a process.The experiments reported in this paper were designed to observe the aerobic and anaerobic metabolism in human platelets during and following interiorization of two different particles, viz. polystyrene latex and thorotrast. The results of these experiments show a marked difference between both types of particles with regard to observable metabolic changes despite the rapid interiorization of both types of material. Some alteration occurs in both aerobic and anaerobic metabolism a considerable time after interiorization of latex, whereas no alteration could be demonstrated after interiorization of thorotrast. It is suggested that the interiorization of particulate matter is by some process other than phagocytosis and that observed metabolic changes related to latex may be due to a release reaction.